Employee Performance is Influenced by Work Motivation and Facilities Infrastructure - Shely Rahmadatul Fitria; Ika Korika Swasti (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2026)
Purpose - This research seeks to examine how work motivation and facilities infrastructure conditions affect the performance of emloyees at PT Z. Design/methodology/approach – This research was conducted directly in the field by gathering information through interviews, observations, and questionnaires. The data obtained was then processed using a quantitative approach. The research respondents included contract employees in the production department, who were selected using a saturated sampling method. Outer and inner model analysis was used with the help of SmartPLS. Originality -  This research has not been conducted previously on the same subject.   Findings and Discussion - The findings of this study indicate that work motivation has a positive and significant effect on employee performance, and that facilities infrastructure also has a positive and significant effect on employee performance. The study’ findings highlight the critical role of wage appreciation and ensuring the availability of adequate work facilities. Conclusion - The study shows that work motivation has a positive effect on employee performance; high work motivation can encourage enthusiasm and commitment to work. In addition, facilities infrastructure also has a positive effect on employee performance. Adequate facilities infrastructure can increase work effectiveness.